2014
DOI: 10.1111/ibi.12136
|View full text |Cite
|
Sign up to set email alerts
|

Foraging guild perturbations and ecological homogenization driven by a despotic native bird species

Abstract: Anthropogenic activities often cause specialized and fragmentation-sensitive species to be replaced by competitive commensal or invasive species, resulting in reduced diversity and biotic homogenization. However, biotic homogenization driven by increased dominance of a native species has rarely been investigated. Increased abundance of competitive species can have important consequences for assemblage dynamics including homogenization of foraging strategies and, potentially, ecological services. This study ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 98 publications
(207 reference statements)
3
22
0
Order By: Relevance
“…For example, in Australia, the native hyperaggressive noisy miner (Manorina melanocephala) attacks most other birds. The resultant population declines of other species led to M. melanocephala being identified as a reverse keystone species by virtue of its subcontinental-scale effect on entire avifauna assemblages [55][56][57].…”
Section: Behavioral Interference In Competition Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Australia, the native hyperaggressive noisy miner (Manorina melanocephala) attacks most other birds. The resultant population declines of other species led to M. melanocephala being identified as a reverse keystone species by virtue of its subcontinental-scale effect on entire avifauna assemblages [55][56][57].…”
Section: Behavioral Interference In Competition Experimentsmentioning
confidence: 99%
“…For example, in Australia, the native hyperaggressive noisy miner (Manorina melanocephala) attacks most other birds. The resultant population declines of other species led to M. melanocephala being identified as a reverse keystone species by virtue of its subcontinental-scale effect on entire avifauna assemblages [55][56][57].Habitat Partitioning and Coexistence The altitudinal replacements examples (above) illustrate how aggressive interference could foster coexistence between species on a regional scale where, in the absence of interference, one species might expand its niche and drive the other extinct [17][18][19]. Similar outcomes are possible on a finer geographic scale when habitats occur in a mosaic of low-and high-quality patches.…”
mentioning
confidence: 99%
“…Further studies are essential to test whether there is an effect of seasons, climate and tree host species. The important role of avian predators in regulating insect community dynamics is emphasised in the current literature with correlated indirect effects on the host plant, such as dieback [26] [68] [72] [73]. However, a possible bias may be reflected here for publishing significant results, as suggested by Low and Connor [74].…”
Section: Resultsmentioning
confidence: 99%
“…[51] [60] [61], as well as data from studies on despotic avian species e.g. [26]- [28], have shown similar effects for canopy arthropods. Our results also showed that the assemblage of the insect canopy community was not significantly affected by bell miner presence.…”
Section: Discussionmentioning
confidence: 98%
“…This may reflect the fact that Manorina honeyeaters often favour more productive areas , which may support more individuals and therefore more species through greater energy and resource availability (Storch et al, 2005;Watson, 2011). Furthermore, noisy and yellow-throated miners tend to have their strongest adverse effects on smaller birds, although they are also associated with increases in larger birds (Howes et al, 2014;Kutt et al, 2015). Thus, it may be that undesirable compositional differences such as site-scale homogenisation of bird communities arise as a result of Manorina occurrence (Howes et al, 2014;Kutt et al, 2015), but that landscape-level species richness may not necessarily be reduced in landscapes with many Manorina honeyeaters.…”
Section: Ecological Mechanisms Moderate the Effect Of Vegetation Areamentioning
confidence: 99%